2013
DOI: 10.1039/c3tb00551h
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal bioimaging using a rare earth doped Gd2O2S:Yb/Er phosphor with upconversion luminescence and magnetic resonance properties

Abstract: While infrared upconversion imaging using halide nanoparticles are so common the search for a very efficient halide free upconverting phosphors is still lacking. In this article we report Gd2O2S:Yb/Er,YbHo,YbTm systems as a very efficient alternative phosphors that show upconversion efficiency comparable or even higher than existing halide phosphors. While the majority of rare earth dopants provide the necessary features for optical imaging, the paramagnetic Gd ion also contributes to the magnetic imaging,ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 47 publications
0
64
0
Order By: Relevance
“…35 In our recent studies, downconversion (Stokes) emission at 1064 nm from fluoride based nanoparticles was detected through a thickness up to 4.93 mm of pig skin under 800 nm excitation compared to that of 1.3 mm for UC emission (red) under 980 nm excitation. 36, 37 These effects may be due to the higher absorption coefficient of water (0.48 cm −1 ) at 980 nm compared to that of 0.02 cm −1 at 800 nm. More importantly, at 800 nm excitation, a larger portion of incident photons is absorbed by hemoglobin, instead of water.…”
Section: Introductionmentioning
confidence: 99%
“…35 In our recent studies, downconversion (Stokes) emission at 1064 nm from fluoride based nanoparticles was detected through a thickness up to 4.93 mm of pig skin under 800 nm excitation compared to that of 1.3 mm for UC emission (red) under 980 nm excitation. 36, 37 These effects may be due to the higher absorption coefficient of water (0.48 cm −1 ) at 980 nm compared to that of 0.02 cm −1 at 800 nm. More importantly, at 800 nm excitation, a larger portion of incident photons is absorbed by hemoglobin, instead of water.…”
Section: Introductionmentioning
confidence: 99%
“…The data clearly showed that the NaOL-coated MNPs were the most magnetic in nature which was again confirmed by measuring the magnetic moment per nanoparticle. By fitting the magnetization curve with the Langevin function [23], the moment per particle was found to be 10,050 μ B , 11,390 μ B , and 14,740 μ B respectively for oleic acid-coated (in solvent), CTAB-coated (aqueous) and NaOL-coated (aqueous) MNPs. For the CTAB-coated MNPs, the saturation magnetization (15 emu/g) was reduced after phase transfer, as compared to the MNPs in solvent (20 emu/g).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is a hypersensitive transition . 2,16,17 The number of the 5 D 0 – 7 F J (J = 1, 2, 3, 4) emission lines is governed by the selection rules, which depend on the local symmetry of the crystal fields around the sites that the Eu 3+ ions occupy. 21 The inset of Fig.…”
Section: Resultsmentioning
confidence: 99%